The origin of Account Planning: the consumer knowledge management in advertising agencies (Communication & Society, 2009)
Account Planning is the discipline that works to integrate the consumer research in the whole advertising process. The aim of this article is to review the main historic events in order to find out the causes of the discipline’s origin in the advertising agencies in 1968, the persons who promoted this change that has been a revolution in advertising. It is necessary to know in depth the consumers to achieve the advertising efficacy. Today it is important to study the past to understand the relevance of these ideas and its repercussion on the current agencies.